Transfer of Assets With Share of Foundations to A Limited Company in The Perspective of The Foundation Act and The Limited Company Law - Sucia, Cut Mira; Ramlan, Ramlan; Perdana, Surya (Veteran Law Review, 2021)
Foundations that run a profit-seeking business are not prohibited as long as the profit-seeking business is not directly carried out by the Foundation, but by establishing a limited liability company. The problem in this thesis is how the position of foundation assets transferred in the form of shares to Limited Liability Companies is examined from the perspective of the Foundation Law and the Limited Liability Company Law, how the process of transferring Foundation assets in the form of shares to Limited Liability Companies is reviewed from the perspective of the Foundation Law and the Limited Liability Company Law. This type of research is normative juridical, namely research based on law. Data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. Drawing conclusions in this paper is done using deductive-inductive thinking logic, which is done with the theory used as a starting point for conducting research. The results showed that the position of the foundation's assets was as the initial assets of the foundation. The process of transferring Foundation assets that is not in accordance with Law Number 28 of 2004 concerning Foundations is if the transfer is carried out by the management of the Foundation without the approval of the Foundation's supervisor and the provisions contained in the Foundation's Articles of Association. The transfer of Foundation assets illegally to shares in a Limited Liability Company is null and void, because it is against the Foundation Law, the Limited Liability Company Law and the provisions of Article 1335 of the Civil Code and 57 paragraph (1) letter b of Law No. 40 of 2007 concerning Limited Liability Companies which require the transfer of shares must obtain prior approval from the company's organs.